Verify that the total differential equation(1+yz)dx+x(z-x)dy-(1+xy)dz=0 is integrable and hence find its integral.
Necessary and sufficient condition for the total differential equation "Pdx+Qdy+Rdz=0"
to be integrable is "P(\u2202R\/\u2202y-\u2202Q\/\u2202z)-Q(\u2202R\/\u2202x-\u2202P\/\u2202z)+\n+R(\u2202Q\/\u2202x-\u2202P\/\u2202y)=0"
"P=1+yz"
"\u2202P\/\u2202z=y"
"\u2202P\/\u2202y=z"
"Q=x(z-x)"
"\u2202Q\/\u2202x=z-2x"
"\u2202Q\/\u2202z=x"
"R=-(1+xy)"
"\u2202R\/\u2202x=-y"
"\u2202R\/\u2202y=-x"
According to the given equation
"(1+yz)(-x-x)-x(z-x)(-y-y)+(-1-xy)(z-2x-z)=\\\\\n=-2x-2xyz+2xyz-2x^2 y+2x+2x^2 y=0"
So it is integrable.
Let "y=const"
"(1+yz)dx-(1+xy)dz=0"
Integrate
"x+xyz-z-xyz=f(y)"
"x-z=f(y)"
Use the equation
"(1+yz)dx+f' (y)dy-(1+xy)dz=0"
"f' (y)=x(z-x)"
"f' (y)=-f(y)x"
"ln\u2061\u3016f(y)\u3017=-xy+C"
"f(y)=exp(-xy+C)"
Answer: "x-z=exp(-xy+C)"
Comments
Leave a comment